Indigenizing Prior Learning Assessment and Recognition: A Review of the Literature - Peyton Juhnke; Tobin LeBlanc Haley (Canadian Journal for the Scholarship of Teaching and Learning)
The purpose of this paper is to provide a review of existing scholarship on the Indigenization of Prior Learning Assessment and Recognition (PLAR). Providing a careful review of this literature contributes a missing map of this field of scholarship and shares key insights for scholars. This is a timely contribution. While the assessment of prior learning has been in practice for decades, this practice has excluded (and continues to exclude) the knowledges of those who remain underrepresented within higher education. In the case of Indigenous learnings, such exclusions are part of the settler colonial operation of post-secondary education that Indigenous scholars and allies are working to disrupt. In order for post-secondary institutions to remain current and adaptive to the ever-changing process of articulating and accrediting knowledge, recognizing and implementing the Indigenization of PLAR is integral. Readers will gain an improved understanding of PLAR, design and implementation considerations when seeking to Indigenize a PLAR process, and examples of well-implemented PLAR for Indigenous learners. As more and more post-secondary institutions consider (to greater and lesser extents) how to address ongoing colonial exclusion of Indigenous knowledges and learners, an Indigenized PLAR process can offer a useful tool. In the settler state of Canada specifically, where the Truth and Reconciliation Commission’s Calls to Action include a focus on providing adequate funding and training so that post-secondary educators can incorporate Indigenous knowledges and teaching methods into the classroom, Indigenized PLAR could potentially support the work of fulfilling this promise. This paper proceeds as follows: 1) a discussion of the search and analysis methodology; 2) a discussion of the importance of Indigenizing PLAR; 3) an overview of key design lessons drawn from the literature; 4) a discussion of important insights in implementation; and 5) a conclusion.